Graphics shaders : theory and practice - Bailey, Mike; Cunningham, Steve (Boca Raton, Florida : CRC Press, 2012)
"This book uses examples in OpenGL and the OpenGL Shading Language to present the theory and application of shader programming. It explains how to program graphics shaders effectively for use in art, animation, gaming, and visualization. Along with improved graphics and new examples and exercises, this edition includes a discussion on handling OpenGL's evolution beyond its original built-in functionality, including four new appendices that provide C++ class code to help in this transition. It includes a new chapter on tessellation shaders. It also discusses shaders in multipass rendering and presents new applications including terrain bump mapping, morphing 3D geometry, and wavy glass."
1. The fixed-function graphics pipeline -- 2. OpenGL shader evolution -- 3. Fundamental shader concepts -- 4. Using glman -- 5. The GLSL shader language -- 6. Lighting -- 7. Vertex shaders -- 8. Fragment shaders and surface appearance -- 9. Surface textures in the fragment shader -- 10. Noise -- 11. Image manipulation with shaders -- 12. Geometry shader concepts and examples -- 13. Tessellation shaders -- 14. The GLSL API -- 15. Using shaders for scientific visualization -- 16. Serious fun
Includes bibliographical references (p. 483-485) and index
Keywords: Computer graphics; COMPUTERS / Computer Graphics; COMPUTERS / Digital Media / Graphics Applications; COMPUTERS / Image Processing; COMPUTERS / Programming / Games; OpenGL; PHOTOGRAPHY / Techniques / Digital; TECHNOLOGY & ENGINEERING / Imaging Systems; Three-dimensional display systems